Preparing for a Changing Climate: The State of Adaptation Planning in Maine’s Coastal Communities - Johnson, Eileen; Stancioff, Esperanza; Johnson, Tora; Sabine, Sarena; Maurice, Haley; Reboussin, Claire (Maine Policy Review, 2019)
Climate change is having a range of impacts on Maine’s coastal communities, impacts that will be further exacerbated by increased coastal flooding, storm events, and a warming Gulf of Maine. To better understand the status of adaptation planning by Maine coastal communities, we conducted a survey and in-depth interviews with decision makers from coastal communities. We found that communities are addressing the effects of climate change and have moved towards specific implementation strategies. Adaptation planning to date includes incorporation of climate change impacts in comprehensive planning and addressing impacts on roads, culverts, and waterfront infrastructure. Respondents indicated the need for more specific data on the direct impacts of climate change in their communities over the next two years. They identified a preference for spatial data and interactive websites, followed by support from technical experts. Although the majority of respondents had an understanding of the physical vulnerabilities their communities face, they identified a need for increased resources to assess social vulnerability impacts. Additionally, communities face challenges in identifying appropriate funding sources that match identified needs. Adaptation planning processes are often stymied by the lack of dedicated funding that enables coastal communities to be proactive in addressing the physical and social impacts of climate change.
Keywords: Gulf of Maine; adaptation planning; interviews; comprehensive planning; infrastructure; social vulnerability impacts